Fucoidan from sea cucumber protects against high-fat high-sucrose diet-induced hyperglycaemia and insulin resistance in mice - Shiwei Hu; Guanghua Xia; Jingfeng Wang; Yuming Wang; Zhaojie Li; Changhu Xue (Journal of Functional Foods, 2014)
The amelioration in hyperglycaemia and insulin resistance of fucoidan from sea cucumber can be speculated due to these effects of fucoidan from marine phaeophyta. We examined the effect of fucoidan from Acaudina molpadioides (Am-FUC) on anti-hyperglycaemia and improvement in insulin resistance in high-fat high-sucrose diet-induced insulin resistant mice. Results showed that Am-FUC significantly reduced blood glucose, insulin, leptin, resistin, and TNF-α levels, and increased adiponectin and hepatic glycogen contents. Am-FUC improved glucose metabolism via an increase in hexokinase and pyruvate kinase activities, and a reduction in glycogen phosphorylase and glucose-6-phosphates activities. Am-FUC enhanced glucose transport through successively activated insulin signalling cascadeinduced GLUT4 translocation. Am-FUC also enhanced the effects of rosiglitazone. No signs of toxicity were observed in acute oral toxicity study. It indicates that Am-FUC acutely reduces blood glucose level and improves insulin resistance via normalization of cytokines and glucose metabolism-related enzyme activities and up-regulation of the PKB/GLUT4 pathway.